A novel fluorene–indolocarbazole hybrid chromophore to assemble high efficiency deep-blue fluorescent emitters with extended device lifetime. Issue 9 (30th January 2020) - Patil, Vilas Venunath; Lee, Kyung Hyung; Lee, Jun Yeob
Abstract : In this work, a novel rigid chromophore was synthesized by the fusion of 9, 9-dimethyl-9 H -fluorene with indolocarbazole (ICz) for the development of deep-blue fluorescent emitters with high efficiencies and long lifetimes. Abstract : In this work, a novel rigid chromophore was synthesized by the fusion of 9, 9-dimethyl-9 H -fluorene with indolocarbazole (ICz) for the development of deep-blue fluorescent emitters with high efficiencies and long lifetimes. The 10, 10-dimethyl-10 H -indeno[2, 1- b ]indolo[3, 2, 1- jk ]carbazole (IDCz ) was utilized as the chromophore for two deep-blue fluorescent emitters synthesized by mono- or di-substitution of electron-donating diphenylamine (DPA) auxochromophore. The systematic investigation of electroluminescence properties of IDCz, IDCz-DPA, and IDCz-2DPA revealed that the external quantum efficiency (EQE), device lifetime, and maximum luminance ( L max ) were increased by increasing the number of DPA units. Moreover, the efficiency roll-off and full width at half maximum (FWHM) were also improved by the DPA substitution. The IDCz-2DPA emitter showed the best performances with a maximum EQE of 5.6%, L max of above 47 000 cd m −2, FWHM of 35 nm with little EQE roll-off at high luminance. Additionally, the IDCz-2DPA emitter outperformed the mono-substituted IDCz-DPA in terms of device lifetime by displaying an augmented lifetime (LT80 : above 140 h) as compared to that of IDCz-DPA (LT80 : 50 h).